Duplication of the vertebral artery: A series of four cases. Issue 6 (December 2018) - Kritikos, Michael; Sharma, Nikhil; Sedora-Roman, Neda; Choudhri, Omar; Pukenas, Bryan; Hurst, Robert; Kung, David
Introduction: Duplication of the vertebral artery (VA) is a rare vascular variant, with less than 50 reported cases in the literature. Case series: We present four cases of VA duplication and discuss the imaging findings, which highlight the rarely seen VA duplication. Discussion: VA duplication is generally considered to be an incidental finding. The VA is formed from the fusion of the longitudinal anastomoses that link the cervical intersegmental arteries, during the 32–40-day stage. The duplication of the VA is a clinically relevant finding for planning of head and neck surgery and neuro-interventional procedures.